Arrested development. Season two [videorecording (DVD)] - Shallat, Lee; Bateman, Jason; De Rossi, Portia, 1973-; Arnett, Will; Cera, Michael; Shawkat, Alia, 1989-; Hale, Tony; Cross, David, 1964-; Tambor, Jeffrey, 1944-; Walter, Jessica, 1941-2021; Hurwitz, Mitchell (Arrested development, 2005)
As his father continues to face legal trouble, Michael Bluth runs the family business, tackling a host of legal and financial issues while trying to cope with his eccentric relatives.